2014
DOI: 10.1136/jfprhc-2013-100724
|View full text |Cite
|
Sign up to set email alerts
|

Trends and patterns of hormonal contraceptive prescribing for adolescents in primary care in the UK

Abstract: BackgroundHormonal contraceptives are the most common method used worldwide by teenagers to prevent unwanted pregnancies. To date there are limited data about such use by teenagers in the UK. This study investigated trends and patterns of hormonal contraceptive prescribing to adolescents aged 12–18 years in UK primary care between 2002 and 2011.MethodsA retrospective cohort study using the IMS Disease Analyzer database was conducted. All females aged 12–18 years with ≥1 prescription for a contraceptive drug be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…We lack the information to differentiate between intentional discontinuation and erratic filling. We also lack information regarding the medical indication for OC use, even though previous studies have shown that among this age group the majority are prescribed OC for contraception as opposed to other indications 33. In other studies11 24 also, adherence of OC was assessed but the indication for OC prescription was not mentioned.…”
Section: Discussionmentioning
confidence: 97%
“…We lack the information to differentiate between intentional discontinuation and erratic filling. We also lack information regarding the medical indication for OC use, even though previous studies have shown that among this age group the majority are prescribed OC for contraception as opposed to other indications 33. In other studies11 24 also, adherence of OC was assessed but the indication for OC prescription was not mentioned.…”
Section: Discussionmentioning
confidence: 97%
“…Not surprisingly, given the graph, the null hypothesis of no difference between prescription rates for older and younger teenagers can be rejected ( p <0.001, Results paragraph 1). In Figure 1 the increase in prescribing across years appears to have been modest,1 and no p value is reported, so presumably there was no statistically significant difference across calendar years.…”
Section: Examplementioning
confidence: 95%
“…historical time, i.e. years 2002 to 2011)1 or between specific subgroup characteristics (e.g. younger and older teenagers) 1.…”
Section: When/why Is It Useful?mentioning
confidence: 99%
See 2 more Smart Citations